Investigation into the kinetics, mechanisms and particle characteristics of selenium precipitation from copper sulphate solution. - Mangere, Murehwa (Department of Chemical Engineering, 2024)
The removal of selenium from copper sulphate solution prior to the electrowinning of copper is desirable in order to minimise contamination of the copper cathodes by selenium and other impurities. The selenium removal is effected by a precipitation process that takes place under high supersaturation conditions which favour nucleation over any other particle formation processes. There is currently no fundamental information on the nucleation kinetics of this important process. Furthermore, the fundamental chemistry and mechanisms involved in this process are not fully understood. In this study, the nucleation kinetics, the process chemistry and mechanisms of selenium precipitation from acidic copper sulphate solution were investigated. Nucleation kinetic experiments were carried out by varying the levels of supersaturation from 8.66x1015 to 4.33x1017 at a temperature of 95°C under atmospheric pressure. The nucleation rates for four different levels of supersaturation, the nucleation work and the nucleus size were determined. The kinetic constant A was found to be 3.92x1027 m-3s-1 and this shows that the nucleation process takes place through a homogeneous mechanism. The associated thermodynamic parameter (B) was determined to be 8.98x10°4. Thermodynamic analysis showed that selenium exists as hydrogen selenate (HSeO4-) and hydrogen selenite (HSeO3-) in the acidic copper sulphate solution. The reduction reactions of these ions using sodium sulphite were predicted to go to completion, precipitating selenium as copper selenide (Cu2Se) at an operating temperature range of 85°C to 100°C. Kinetic studies of selenium reduction revealed that the reduction of selenium (+4) ions is very fast (99.9% conversion achieved in less than 60 seconds). However, the reduction of selenium (+6) is very slow (only 45.7 % conversion achieved in 72 hours). During the reduction of selenium(+6), a brick red precipitate, which is a mixture of element copper and Chevreul's salt (Cu2SO3.CuSO3.2H2O) is also be formed. A theoretical study was carried out to explain the differences in the reactivity of these selenium species. The results revealed that selenate has zero dipole moments and has a rigid molecular structure which makes it 'unreactive'. Activation energy calculations also showed that selenate has a higher transition state barrier ( 4.354 kcal/mol) as compared to University of Cape Town the selenite (3.054 kcal/mol). However, acidifying the solution resulted in a protonated selenate ion which significantly altered the molecular structure of the selenate ion. The results also showed that the interaction between protonated selenate and sulphite ions has a lower transition state barrier (3.914 kcal/mol) than for the free selenate system.